Caracterização microestrutural, eletroquímica e tribológica de revestimentos HVAF Fe₆₈Cr₈Mo₄Nb₄B₁₆ - Mota, Igor Gabriel Coinete (Universidade Federal de São Carlos, 2023)
High corrosion and wear resistance are basic requirements for materials that operate in aggressive environments such as those found in the petrochemical, mining and agro-industry industries. Fe-Cr-B-based vitreous/nanocrystalline alloys are well-established candidates for applications where high corrosion and wear resistance are required, as the Cr-rich vitreous matrix allows passivation, while the hard, refined borides ensure the die protection against wear. Recent and pioneering works carried out at DEMa UFSCar have developed ferrous and nanocrystalline coatings, produced by thermal spray, resistant to wear and corrosion. Both corrosion in saline media (acidic and basic) and wear (abrasive and sliding) were investigated, indicating excellent performance and durability compared to carbon and stainless steels. In addition to the interesting combinations of chemical and physical properties, these alloys are relatively low-cost systems and, therefore, are viable from an economic point of view. The present master's thesis investigated the microstructure of the FeCr alloy coating produced by High Velocity Air-Fuel process (HVAF) through the use of commercially pure elements and powders produced by gas atomization, and their evaluation to corrosion and wear. The coating produced was characterized by optical microscopy (OM), confocal microscopy (CM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X ray diffractometry (XRD), differential scanning calorimetry (DSC), wear tests (Standard Test ASTM G133-05), corrosion tests (potentiodynamic polarization), hardness and porosity measurements. The results obtained indicated good corrosion resistance of the coating against the substrate (SAE 1020) and the ingot, however, due to the wear mechanisms present during the tests and the characteristics arising from the deposition process used, the coating showed low wear resistance.
Microstructural, electrochemical and tribological characterization of HVAF Fe₆₈Cr₈Mo₄Nb₄B₁₆ coatings
Keywords: Aço; Ligas vítreas/nanocristalinas; HVAF; Revestimento; Corrosão; Desgaste; Steel; Glassy/nanocrystalline alloys; Coating; Corrosion; Wear; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA